2015
DOI: 10.1007/s13312-015-0570-9
|View full text |Cite
|
Sign up to set email alerts
|

Malignant rhabdoid tumor of kidney and brain in an infant

Abstract: Children presenting with embroynal brain tumor, should be investigated for renal tumors and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It has been suggested that the origin could be from primitive cells in the renal medulla. Rhabdoid tumors of the kidney consist of cells organized in diffuse sheets, alveolar or trabecular patterns [4,5].…”
Section: Case Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the origin could be from primitive cells in the renal medulla. Rhabdoid tumors of the kidney consist of cells organized in diffuse sheets, alveolar or trabecular patterns [4,5].…”
Section: Case Discussionmentioning
confidence: 99%
“…Lack of immunohistochemical staining for SMARCB1 gene (also known as SNF5, INI-I, or BAF47) support histologic diagnosis of malignant renal rhabdoid tumors. Inactivating both copies of a gene by deletions or mutations at chromosomal location 22q11.23 cause biallelic inactivation of SMARCB1 tumor suppressor gene [4,5,7].…”
Section: Discussionmentioning
confidence: 99%